2016
DOI: 10.1007/s10597-015-9985-y
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Predictors of Depression in Type 2 Diabetic Population of Punjab

Abstract: The present cross sectional study was carried out on 787 type 2 diabetic subjects from tertiary health care hospitals to identify the prevalence and predictors of depression in diabetes. Depression was tested using Patient Health Questionnaire-9. Of the study participants, 199 (25.29%) met the criteria for mild to moderate depression, 252 (32.02%) were severely depressed and 336 (42.69%) were clinically non-depressed. The prevalence of depression was 65.02 % in women, which is 1.87 fold higher (p < 0.0001) tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 45 publications
2
14
0
Order By: Relevance
“…Page 1311 be 32.56% is comparable with previous findings in Northern India 41%, Netherlands 31%, in Bahrain 33.3%, in Malaysia 30.5%, A multi-center study done in Pakistan found prevalence as 43.5% [9][10][11][12][13]. …”
supporting
confidence: 84%
“…Page 1311 be 32.56% is comparable with previous findings in Northern India 41%, Netherlands 31%, in Bahrain 33.3%, in Malaysia 30.5%, A multi-center study done in Pakistan found prevalence as 43.5% [9][10][11][12][13]. …”
supporting
confidence: 84%
“…[ 18 ] In general, our finding is smaller than distinct discoveries from Maroc, Guinea, Nigeria, Asia, Nepal, Bangladesh, and India. [ 7 12 13 14 15 16 25 26 27 ] These distinctions can be due to the differences in sample size, sociodemographic condition, and others.…”
Section: Discussionmentioning
confidence: 99%
“…Across the globe distinct, prevalence rates have been reported on depression among diabetic patients; this includes higher figures of 59.8%,[ 11 ] 50–60% in Asia,[ 12 13 ] 54.1% in Nepal,[ 7 ] 45.2% in Bangladesh[ 14 ] to (25.3–35.4%) in India,[ 15 16 ] 17% in Poland,[ 17 ] and substantially lower rate of 11.2% in Peru. [ 18 ]…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations